(untitled) (REVUE ROUMAINE DES SCIENCES TECHNIQUES — SÉRIE ÉLECTROTECHNIQUE ET ÉNERGÉTIQUE, 2024)
In this work, the maximum power point (MPP) of a photovoltaic (PV) array utilized as a source of electricity in standalone mode is tracked using a genetic algorithm (GA) as an optimization tool. The major objective of this work is to implement and regulate a six-phase induction motor (SPIM) powered by a centrifugal pump and fed by a perovskite solar array through a three-phase inverter. Perovskite solar cells are the most promising third-generation photovoltaic technology to replace silicon-based photovoltaic. These cells are made cheaply, at a low temperature, and efficiently. The outcomes are then investigated utilizing a SPIM scaler (v/f) closed-loop control. PID controllers are tuned to keep the motor speed aligned with the reference value. The transformer’s six-phase secondary is linked to an LC filter to reduce the voltage and current waveform ripple. A test setup was created and installed to investigate the potential of controlling the SPIM fed via a three-to-six-phase transformer. The findings showed that the area needed for the plates when utilizing perovskite solar cells is just 14 % of what it would be if a silicon-based solar array were used for the identical purpose. Perovskite solar cells’ tiny surface area helps to prevent partial shading and lower costs. It was discovered that the suggested method works well for powering SPIM from a three-phase source.